The Development of Interactive Multimedia Career Information for Students at SMKN 1 Mandau - Izzah Mardhiyah Murassyidah; Khairiyah Khadijah; Isnaria Rizki Hayati (Yayasan Corolla Education Centre, 2026)
Access to career information for students that is still presented in a conventional and less engaging manner has the potential to reduce students’ involvement in the career exploration process optimally. This study develops interactive multimedia career information as a supporting medium designed to facilitate students’ career exploration needs, so that students can actively participate in exploring, selecting, and understanding information that is relevant to their interests and career plans. The purpose of this study is to produce an interactive multimedia career information product and to analyze the feasibility of the product in terms of validity and practicality. This study uses a Research and Development (R&D) approach with the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. This research focuses on product development and feasibility testing (validity and practicality) at the initial implementation stage; therefore, testing the effectiveness of the product in improving career exploration is not included within the scope of this study. The results show that the developed interactive multimedia has a validity level with an average score of 96.23%, categorized as very valid, and a practicality level with a score of 92.21%, categorized as very practical. These findings confirm that the developed interactive multimedia career information is feasible to be used as a career information medium to support the career exploration of vocational high school students.